Studi Kualitatif: Penerapan Model Problem Based Learning pada Materi Peran Makhluk Hidup dalam Rantai Makanan - Devika Sri Yunda; Nurul Fadhli; Halimah; Rieke Alyusfitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the application of the Problem-Based Learning (PBL) model to science instruction on the role of living things in the food chain in elementary schools. The study used a qualitative approach with a case study design, conducted at SDN 03 Alai. Subjects included classroom teachers and students directly involved in the learning process. Data were collected through in-depth interviews, learning observations, and documentation studies. Data analysis was conducted using an interactive analysis model, encompassing data reduction, data presentation, and conclusion drawing. Its validity was tested through triangulation of sources and techniques. The results showed that the implementation of the PBL model created a more active, contextual, and student-centered learning environment. Students demonstrated high engagement in group discussions, a more meaningful understanding of the food chain concept, and increased interaction and collaboration among students. However, the implementation of PBL still faced challenges in time management and differences in student participation levels. This study concluded that PBL has the potential to improve the quality of science instruction in elementary schools if supported by careful planning and effective classroom management